Temporal Case-Based Reasoning Model for Reservoir Spillway Gate Operation Recommendation - Mohd Hafiz, Mohd Hassin (2008)
Emergency decision making process faces difficulty in making timely and right decision. Delay in decision making will result catastrophic events that will jeopardize the public safety and properties. Decision making in reservoir spillway gate operation is usually dynamic in nature, and requires expert experiences in order to deliver decision. In this research, a decision support system was proposed that can assist decision maker determining whether to open or close the spillway gate. In this thesis, the Temporal Case-Based Reasoning (TCBR) technique is implemented to model the dam technician knowledge, by utilizing experiences database (case-base), to solve future problems. This is an experimental study, where Knowledge Discovery in Databases (KDD) approach is integrated with General Methodology of Design Research (GMDR), where a prototype was developed to proof the proposed model. Timah Tasoh Dam operation data ranges from year 1998 to 2005 are used to serve as a case study in this model. The proposed model was found to be able to recommended decision with up to accuracy of 87.2 percent and 88.75 percent case similarity with previous cases.